2018
DOI: 10.1001/jama.2018.11439
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Spending on Brand-name Combination Medications vs Their Generic Constituents

Abstract: IMPORTANCE Brand-name combination drugs can be more expensive than the sum of their components, especially when the constituent products are available as generic medications. The potential savings that could be achieved using generic components is not known.OBJECTIVE To estimate the additional cost to Medicare of prescribing brand-name combination medications instead of generic constituents. DESIGN, SETTING, AND PARTICIPANTSRetrospective analysis for 2011 through 2016 using the Medicare data set of Part D bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…In a retrospective study carried out in the USA, investigating Medicare spending on brand-name combination medications vs their generic constituents, it was found that medical expenses were higher for brand-name combinations compared with generic constituents. 16 A similar study in Japan would be required to confirm whether the findings are applicable. Another disadvantage to FDC is the fact that the agents are taken simultaneously, which means that chronotherapy with a particular agent cannot be used.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a retrospective study carried out in the USA, investigating Medicare spending on brand-name combination medications vs their generic constituents, it was found that medical expenses were higher for brand-name combinations compared with generic constituents. 16 A similar study in Japan would be required to confirm whether the findings are applicable. Another disadvantage to FDC is the fact that the agents are taken simultaneously, which means that chronotherapy with a particular agent cannot be used.…”
Section: Discussionmentioning
confidence: 94%
“…As well as not being able to make dose adjustments when using FDC, another disadvantage might be cost when compared with the use of generic multi‐pill combinations. In a retrospective study carried out in the USA, investigating Medicare spending on brand‐name combination medications vs their generic constituents, it was found that medical expenses were higher for brand‐name combinations compared with generic constituents . A similar study in Japan would be required to confirm whether the findings are applicable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I selected the topic of assumptions for this month's Note because of a recent article I read. Sacks et al 21 published their paper, Medicare Spending on Brand-name Combination Medications vs Their Generic Constituents, in a July issue of the JAMA. Using 2016 data, they concluded that medication costs could be reduced through better prescriber education and by using appropriate generic and therapeutic substitutions.…”
Section: Therapeutic Substitutionmentioning
confidence: 99%
“…For the treatment of hypertension, Sacks et al 21 propose substituting generic losartan, an angiotensin receptor competitive antagonist, for the more expensive, brand-named azilsartan (Edarbi), also an angiotensin receptor competitive antagonist, with either of these drugs given in combination with chlorthalidone, a generically available, long-acting thiazide diuretic. Readers who remember mechanisms of action may recall that angiotensin receptor competitive antagonists inhibit the binding of angiotensin II to its receptor, which, in turn, inhibits the reabsorption of sodium chloride (salt) from the proximal tubule of the kidney.…”
Section: Therapeutic Substitutionmentioning
confidence: 99%